ESTRUCTURA DE LA COMUNIDAD Y DINÁMICA POBLACIONAL DE GASTERÓPODOS EN UNA ZONA ENZOÓTICA DE FASCIOLOSIS EN TABASCO, MÉXICO - Rangel Ruiz, Luis José; Gamboa Aguilar, Jaquelina (Instituto de Ecología, A.C., 2005)
In an endemic area of fasciolosis in the municipality of Teapa in the state of Tabasco we analyzed the gastropods associated with Lymnaea viatrix, their community structure, the population dynamics of the most important species, and their relationships with climatic parameters. The gastropod community consisted of nine species, two Prosobranchia: Pomacea flagellata (Say 1929) and Triodopsis sp, and seven Pulmonata: L. viatrix, Biomphalaria obstructa (Morelet 1849), Drepanotrema lucidum (Pfeiffer 1839), Stenophysa impluviata (Morelet 1849), Succinea undulata (Say 1829), Drymaeus corneus (Sowerby 1833) and Belocaulus angustipes (Heynemann 1885). Patterns of species diversity and evenness behaved similarly. Lymnaea viatrix and B. obstructa showed the highest average values of relative abundance (39.58 and 42.58 %), relative frequency (18.69 and 18.69 %), relative dominance (41.76 and 44.92 %) and importance (100.01 and 106.17). The highest density of organisms was observed in December 1989 (L. viatrix with 24.2, B. obstructa with 58.0 and S. impluviata with 15.3 individuals/m²), the lowest during aestivation (April to June of 1989 and May of 1990). Stenophysa impluviata was the only species whose population size correlated positively to precipitation intensity and frequency and negatively to temperature. Stenophysa impluviata was the only species in which its population's size varied directly proportional for the precipitation and precipitation frequency and inversely proportional for the temperature.